Magis belantara herba orang asli : katalog pameran. - Malaysia. Jabatan Muzium (Kuala Lumpur : Jabatan Muzium Malaysia, 2010)
Medicinal plants for traditional herbal medicine used by Orang Asli in Malaysia; catalog of an exhibition.
Keywords: Medicinal plants -- Catalogs; Herbs -- Therapeutic use